Are Job Search Programs a Promising Tool? : A Microeconometric Evaluation for Austria - Andrea Maria Weber; Helmut Hofer (Institute for the Study of Labor (IZA), 2004)
In Austria job search programs were introduced on a large scale in 1999. These programs aim at activating unemployed at an early stage and bringing them back to work by training job search related skills. We evaluate the impact of active labour market programs in Austria on individual unemployment durations, and allow program effects to vary between job search programs and formal training programs. We use the timing-of-events method which estimates the program effect as a shift in the transition rate from unemployment to jobs at the moment of program entry. We find that participation in job search programs significantly reduces unemployment durations, whereas formal training programs have a negative effect on unemployment durations.
Keywords: C14; J68; J64; C41; 330; active labour market policy; treatment effect; multivariate duration model; Arbeitsuche; Arbeitsmarktpolitik; Berufliche Integration; Wirtschaftspolitische Wirkungsanalyse; Schätzung; Österreich; treatment effect